Congenital CMV Infection: A Complex Case of Neurological Complications and Therapeutic Approaches in Infancy - Koziej, Sylwia; Kowalczyk, Emilia; Niemczuk, Martyna; Jasiuk, Adrianna; Wiekiera, Mateusz (Journal of Education, Health and Sport, 2024)
Introduction and purpose Congenital Cytomegalovirus (CMV) infection stands as the prevalent infection among newborns and it may be associated with later complications such as progressive sensorineural hearing loss or neurological diseases. Infection occurs during pregnancy or during childbirth. Congenital CMV infections manifest in various ways, ranging from asymptomatic cases to severe complications such as microcephaly, hepatosplenomegaly, and chorioretinitis. Routine antibody screenings for pregnant women are not common, underlining the significance of early infection detection to minimize the risks of transmission to the fetus and potential complications in the child. The aim of this case report is to present the course of congenital CMV infection and its complication. This case report explores the challenges of managing an infant with congenital CMV infection complicated by hydrocephalus and viral co-infections. The infant underwent various treatments, including antiviral therapy, highlighting the need for multidisciplinary approaches. Conclusion With no available vaccine, prevention of congenital CMV infection relies on educating reproductive-age women and expectant mothers about infection risks. Early detection, frequent medical check-ups, and preventive education are crucial due to the absence of vaccines. Ongoing exploration of antiviral treatments and prompt interventions is imperative to improve outcomes for infants and families affected by the virus.